MERMIS SP. (NEMATODA: MERMITHIDAE) AS A PARASITE OF ZONOCERUS VARIEGATUS LINNAEUS (ORTHOPTERA: PYRGO MORPHIDAE) - MATANMI, BABAJIDE A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Memis sp. (Nematoda: Mermithidae) was consistently encountered in dissected specimens of Zonocenus variegatus (Linnaeus) collected at random from the filed in the Ile-Ife area of Nigeria. In this study, parasitization at different locations ranged between 0 to 7.58%. Although this parasite may constitute an important factor in the mortality of Z. variegatus, it does not appear to be efficient as a potential biological control tool.